POLITIK HUKUM PENGADOPSIAN RESTORATIVE JUSTICE DALAM PEMBAHARUAN HUKUM PIDANA - septa chandra (Universitas Lampung, 2014)
The purpose of this study was to find a political choice of law in criminal law reform. Using a juridical approach using secondary data, it can be concluded that the legal political reform criminal law in Indonesia is still ongoing and to be part of the development of the national legal system. Legal political development of the national legal system should be based on Pancasila as a guide and tool for political filtering of national law and UUDNRI 1945 Constitution as the basic law. One form of political reform criminal law is by adopting the concept of restorative justice as an alternative mechanism for the settlement of legal issues that occur without the use of judicial proceedings. With the approach of restorative justice, the enforcement of which has always used retributive approach (retaliation) would merely shift to restorative approaches (recovery). The concept of restorative justice can be political legal permanent (permanent) in building the national criminal justice system that will come.Keywords: Politics Law, Restorative Justice and Criminal Case